The determinants of influence purchase intention to buy residential property in Bandar Dato’ Onn / Nassyuha Assyillah Abdul Samad - Abdul Samad, Nassyuha Assyillah (Faculty of Business Management, 2017)
This research is to fulfil the requirement of IBM 627 Research Method is done by a student of Bachelor in Business Administration (Hons) International Business in order to complete the Bachelor Program. The tittle of this research is “The Determinants of Influence Purchase Intention towards a Residential Property in Bandar Dato’ Onn”. It is also a project that assembles the intellectual interest and critical thinking of the student. This enhances the integrations of capabilities and abilities of the postgraduates in the application of theoretical elements. The main purpose of this research project is to investigate the independents variables that affect the Purchase Intention towards a Residential Property in Bandar Dato’ Onn. Based on the previous research by Kok Chin San (2016), throughout this project, there are three dependent variables has been identified which are Property View (PV), Property Attribute (PA) and Property Surrounding (PS) and independent variables which is Purchase Intention (PI). The purpose of the study was to examine the purchase intention towards residential property in Bandar Dato’ Onn. The data for this study was collected using a survey questionnaire. For this research, the target populations were the customers that walk into the sales gallery of Johor Land in Bandar Dato’ Onn and random house owner in Bandar Dato’ Onn. As the targeted 100 respondents data were collected and been processed in SPSS 20.0 software. The outcome from the research are Property Attributes (PA) play a major role in purchase intention of customer to buy the residential property in Bandar Dato’ Onn and followed by the Property Surrounding (PS).